Behavior and susceptibility to stress corrosion cracking of a nickel‐based alloy in superheated steam and supercritical water. Issue 1 (26th July 2018) - Khan, Hasan Izhar; Zhang, Naiqiang; Zhu, Zhongliang; Jiang, Dongfang; Asif, Tahir; Xu, Hong
Abstract : Stress corrosion cracking (SCC) behavior of Alloy 617 was studied to evaluate its suitability for Generation IV supercritical water reactor concept. A series of slow strain rate tensile (SSRT) tests at a constant strain rate of 5 × 10 −7 s −1 were carried out in superheated steam and supercritical water over a pressure range of 0.1–25 MPa at 650 °C. SSRT test in dry N2 gas was also performed to compare the results in non‐corrosive environment with corrosive medium environment. Intergranular cracks were observed for all specimens regardless of the test environment. Alloy 617 showed susceptibility to SCC at the tested experimental conditions. The dominance of intergranular SCC was observed on the gage surface and fracture surface by using scanning electron microscope analysis. The effect of varying environmental conditions on SCC susceptibility is further discussed. Abstract : Stress corrosion cracking (SCC) behavior of Alloy 617 was studied to evaluate its suitability for Generation IV supercritical water reactor concept. A series of slow strain rate tensile (SSRT) tests at a constant strain rate of 5 × 10 −7 s −1 were carried out in superheated steam and supercritical water. Intergranular cracks were observed for all specimens regardless of the test environment.